The Development of Infant Discrimination of Affect in Multimodal and Unimodal Stimulation: The Role of Intersensory Redundancy - Flom, Ross (2007)
This research examined the developmental course of infants’ ability to perceive affect in bimodal (audiovisual) and unimodal (auditory and visual) displays of a woman speaking. According to the intersensory redundancy hypothesis (L. E. Bahrick, R. Lickliter, & R. Flom, 2004), detection of amodal properties is facilitated in multimodal stimulation and attenuated in unimodal stimulation. Later in development, however, attention becomes more flexible, and amodal properties can be perceived in both multimodal and unimodal stimulation. The authors tested these predictions by assessing 3-, 4-, 5-, and 7-month-olds’ discrimination of affect. Results demonstrated that in bimodal stimulation, discrimination of affect emerged by 4 months and remained stable across age. However, in unimodal stimulation, detection of affect emerged gradually, with sensitivity to auditory stimulation emerging at 5 months and visual stimulation at 7 months. Further temporal synchrony between faces and voices was necessary for younger infants’ discrimination of affect. Across development, infants first perceive affect in multimodal stimulation through detecting amodal properties, and later their perception of affect is extended to unimodal auditory and visual stimulation. Implications for social development, including joint attention and social referencing, are considered.